The Influence of Clean Water Source, Knowledge, Attitudes and Actions of Mother’s Personal Hygiene on the Incidence of Diarrhea in Toddlers in Medan City 2023 - Sufia Idya; Nurmaini Nurmaini; Taufik Ashar (Journal of Social Research, 2023)
Diarrhea is a health problem that globally contributes to the death rate of two billion children worldwide, WHO reports more than 525,000 cases in toddlers are caused by diarrhea. Riskesdas 2018 found that the prevalence of diarrhea among toddlers in Indonesia was 73,188 cases. Medan City in 2020 had 4,561 cases of diarrhea and in 2021 there were 18,588 cases of diarrhea in toddlers. To analyze the effect of clean water source, knowledge, attitudes and actions of mother’s personal hygiene on diarrhea in toddlers. The type of this research is a quantitative study with a cross sectional design. Data analysis used multiple logistic regression tests with a sample of 120 mothers with toddlers aged 2-5 years. The variables that had an effect on were the mother's knowledge (p=0.042) and actions (p=0.019) of personal hygiene on the incidence of toddler diarrhea. Meanwhile clean water (p=0.362) and attitudes (p=0.115) had not effect on the incidence of toddler diarrhea. The variable that has the most influence on the incidence of diarrhea in toddlers in Medan City is the mother's personal hygiene action which have the highest Exp.B value of 2,792. Knowledge and actions of mother’s personal hygiene had influence on the incidence of toddler diarrhea. Further action for officers to be able to carry out health promotion and education regarding basic sanitation and personal hygiene to mothers whose toddlers experience and do not experience.